Feelings Related to the COVID-19 Pandemic Among Patients Treated in the Oncology Clinics (Poland) - Grajek, Mateusz; Działach, Eliza; Buczkowska, Marta; Górski, Michał; Nowara, Elzbieta (Frontiers in Psychology, 2021)
Background. The number of cancer patients is constantly growing. Both WHO and IARC report that this number may reach up to 24 million new diagnosed cases in the next two decades. The proposed treatment and especially the diagnosis can have a significant impact on an individual's approach to the disease, as well as on the patient's quality of life. Objectives. The aim of the study was to assess the quality of life, feelings and fear of cancer-treating oncological patients, before and during the COVID-19 pandemic. Material and methods. The study used the standardized WHOQOL quality of life questionnaire in a shortened version, the COVID-19 fear scale (FCV-19S) and the AIS disease acceptance scale (in terms of cancer-related sensations). The questionnaire survey was conducted among patients of cancer clinics (Poland). The study was conducted in two stages - before the COVID-19 pandemic (May 2019) and during the COVID-19 pandemic (May 2020). Data from 450 correctly completed questionnaires were analyzed statistically. The obtained data were statistically processed using the Kruskal-Wallis and Mann-Whitney U test (p=0.05). Results. Among the surveyed patients of the cancer clinic, the quality of life during the COVID-19 pandemic decreased by 2%, compared to the period before the pandemic. The frequency of negative feelings associated with cancer increased during the COVID-19 pandemic - by 11% more men, and 4.4% of women determined the frequency of negative feelings to be 2-3 times a week. The level of fear associated with COVID-19 was moderate (57.1%), with women having a higher level of fear (12.5% higher than men). Conclusion. The development of the epidemic is very important in terms of public health. COVID-19 should be considered as one of the factors that bring about sudden changes in the mental health of the population, which may result from the dynamic development of this disease, dramatic media coverage and own experiences. It has been shown that the sudden appearance of such a large stressor causes a decrease in patients' quality of life and an increase in negative feelings associated with chronic disease.